2020
DOI: 10.3390/ma13204670
|View full text |Cite
|
Sign up to set email alerts
|

Stribeck Curve of Magnetorheological Fluid within Pin-on-Disc Configuration: An Experimental Investigation

Abstract: The paper focuses on the coefficient of friction (COF) of a magnetorheological fluid (MRF) in the wide range of working conditions across all the lubrication regimes—boundary, mixed, elastohydrodynamic (EHD), and hydrodynamic (HD) lubrication, specifically focused on the common working area of MR damper. The coefficient of friction was measured for MR fluids from Lord company with concentrations of 22, 32, and 40 vol. % of iron particles at temperatures 40 and 80 °C. The results were compared with a reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The distance between the magnetic poles was w = 1 mm. The core assembly reveals two magnetic pole pieces (4), the bronze non-magnetic spacer (5), and the air gap (6). The purpose of the air gap (size −0.8 mm) was monitoring the flux in the magnetic circuit with the Hall probe.…”
Section: Mr Pinch Valve Prototypementioning
confidence: 99%
See 1 more Smart Citation
“…The distance between the magnetic poles was w = 1 mm. The core assembly reveals two magnetic pole pieces (4), the bronze non-magnetic spacer (5), and the air gap (6). The purpose of the air gap (size −0.8 mm) was monitoring the flux in the magnetic circuit with the Hall probe.…”
Section: Mr Pinch Valve Prototypementioning
confidence: 99%
“…The carrier fluid is chemically compatible with the particles, exhibits low thermal expansion, excellent lubricity, acceptable viscosity across a wide operating temperature range. Moreover, specific additives affect the rheological [2,3] or tribological [4,5] properties of MR fluids as well as improve their sedimentation stability [6,7]. In the presence of magnetic field the ferromagnetic particles in the fluid are magnetized and form chain-like structures along the magnetic flux lines, thus resisting the fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…The particles are spherical and average size (diameter) is 2.1 µm. The particle distribution is according Q3 [35]. The particle material is carbonyl iron.…”
Section: Test Samplementioning
confidence: 99%
“…All the experiments were performed at room temperature (25 • C). Some studies have tested the Stribeck curves of some commercial MRFs, and found that MRF is mainly in the boundary lubrication state [45]. Therefore, the lubrication performance of base oil was also studied based on Stribeck curve…”
Section: Friction Experimentsmentioning
confidence: 99%